Organizing professional work and services through institutional complexity – how institutional logics and differences in organizational roles matter. (February 2022) - Høiland, Gry Cecilie Lunder; Klemsdal, Lars
How is the complexity of contemporary professional work and services organized differently by management at the strategic level and professionals at the operational level? And what are the implications for managing this complexity? Drawing on literatures on institutional complexity, organizational roles and the analyses of case study data from interviews, observations and documents at a large public service provider in Norway, this article advances the understanding of management in complex organizations and makes the following three contributions to the institutional logics literature. First, we show how multiple institutional logics have different functions at strategic and operational levels, resembling a dynamic interplay in organizing professional work and services. Second, we show how these differences in handling multiple logics are contingent upon the different roles of the strategic managers and operational professionals. Finally, we advance the understanding of what institutional complexity may involve in organizations by disclosing how the significant conflicts stem not only from the presence of multiple logics, but also from differences within the organizations in how multiple logics are handled. Our findings have implications for the planning and management of organizational design and implementation strategies and demonstrate the utility of the institutional complexity perspective for managing complexity in contemporary organizations.